MODEL FOR DEVELOPING PROFESSIONALISM IN FUTURE PRIMARY SCHOOL TEACHERS - Salaeva Muborak Saburovna; Berdibekova Feruza Abdumannob kizi; Tulkuniy Madina Turob zoda (The Bioscan, 2025)
The ongoing changes in the socio-economic, spiritual and political realm of our society have not left education - or its central figure, the teacher -unaffected.